Improved completing-treatment support among tuberculosis support group members through the CERMAT (Smart Against TB Transmission) program - Atuti Yuni Nursasi; I Gusti Ayu Putu Desy Rohana; Utami Rachmawati; Rezky Mulyana (Journal of Community Empowerment for Health, 2022)
Tuberculosis (TB) was declared a global emergency for humanity by the World Health Organization in 2015. According to Global Report TB data in 2016, Indonesia is one of the 30 countries in the world that has the highest TB caseload, especially Human Immunodeficiency Virus (HIV)-TB and (Multi Drug Resistant Tuberculosis (MDR) TB) cases during the 2016-2020 period (Global Tuberculosis Report, 2016). The high rise of MDR TB cases has great potential for transmission and an increase in the number of new TB cases. Efforts to optimize the handling of care and treatment, as well as to accelerate the determination of the diagnosis need to be conducted vigilantly on all lines, especially efforts to increase the ability to prevent transmission, provide quality follow-up care, and community-based treatment. Forming support groups is one of community health nursing strategies for TB prevention. A support group provides assistance to increase TB medication adherence and reduce TB transmission. TB control strategies are conducted by implementing CERMAT (Smart Against TB Transmission) to TB support groups that combine education intervention and skills to prevent TB transmission in the community setting. Community health nursing though the nursing process has established a system with recognition of the variables that affect health status and individual behaviors against TB disease. The nursing strategy intervention in the community is done at all levels, such as health education, group process, partnership, and community empowerment. The CERMAT package implemented in the TB support group is an evidence-based nursing practice. It was applied to 70 samples of adult TB clients at Curug, Cimanggis, Depok. The sampling was selected with a non-probability quota sampling technique. This study used an experimental design with paired t-test data analysis to determine the improvement in the skills of the TB support group after the support group intervention was done. It showed there was influence of the CERMAT method on the level of good support for completing TB treatment in Curug Village, with increased the mean of completed treatment by 2.42 with a p value 0.00 (p <0.05). The CERMAT method can be applied as one of the nursing interventions to increase TB clients’ adherence. This intervention can be done by the person who is responsible for the TB program at the Community Health Center. The CERMAT method needs to be continued and evaluated regularly by involving health care volunteers.